Financing and Health System Capacity for Precision Medicine in Asia: A Six Country Landscape Analysis - Adena Li Tyin Peh; Yot Teerawattananon; Jeanette Xue Yan Yuen; Nordin Charafi; Dicky Levenus Tahapary; Jiahua Leng; Alec Morton; Sheyu Li; Woo Jin Kim; Bin Alwi Zilfalil; Hidayati Husainy Hasbullah; Nusara Satproedprai; et al. (Health Affairs Scholar, 2026)
Abstract Background Precision medicine (PM) adoption is accelerating across Asia, but implementation remains uneven due to differences in financing, infrastructure, governance, and health-system readiness. Objectives To examine how six Asian countries (Singapore, South Korea, China, Malaysia, Thailand, and Indonesia) adopt, finance, and integrate PM technologies, and identify common implementation patterns and challenges. Methods A landscape review of peer-reviewed literature, government publications, and HTA reports (2010–2026) was conducted, supplemented by stakeholder consultations. PM applications were grouped into public health screening (hereditary breast and ovarian cancer [HBOC] and familial hypercholesterolemia [FH] cascade testing), next-generation sequencing (NGS) applications (rare diseases, oncology, pharmacogenomics), and AI-enabled PM. Evidence was synthesized across access, awareness, reimbursement, and implementation. Results Public health genomic screening demonstrated the highest implementation readiness, followed by precision oncology, while rare disease diagnostics remained infrastructure-dependent and pharmacogenomics and AI-enabled PM platforms were at earlier stages. Four readiness profiles emerged: highly aligned systems; reimbursement-constrained systems with strong governance and infrastructure; systems strengthening governance, public financing and infrastructure; and strategy-led systems expanding implementation through pilot programs and referral centers. Conclusions PM implementation across Asia remains heterogeneous. The identified readiness profiles highlight governance, financing, and infrastructure priorities for sustainable and equitable PM diffusion.